Validation of the National Disability Rating Criteria for the Elderly with Long-term Care: a hierarchical model-based empirical analysis - Yuanping ZHAO; Rui DING; Hong XIE (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo verify the reliability and rationality of the National Disability Rating Criteria for the Elderly with Long-term Care - Trial Edition using hierarchical model. MethodsUsing complex sampling method and a self-designed questionnaire, we conducted face-to-face interview and onsite assessment among 9 577 long-term caretakers aged 60 years and above in urban nursing facilities in 23 cities of 12 provincial level administrative divisions across various geographical areas in China during March 2022. The collected data were analyzed with analytic hierarchy process, rank sum ratio method and paired Chi-square test to comprehensively evaluate the long-term caretakers' disability degrees and to compare the evaluations with those based on the national criteria. ResultsFor the 9 577 valid participants averagely aged 81.43 ± 8.46 years, 80.0% were assessed as having disability and 47.0% as having moderate and severe disability. A four-level hierarchical model was established based on the regression equation (weighted rank-sum ratio [WRSR] = - 0.5679 + 0.2097 × probit) obtained with analytic hierarchy process and rank sum ratio method. Paired comparison with the original hierarchical model, the Kappa value of the analysis was 0.540 (P < 0.001) and the value of McNemar-Bowker test was 3 376.471 (P < 0.001). There were some differences between the two hierarchical models, and the overall coincidence rate between the two models was 63.6% although there were some differences. Of all the elderly long-term caretakers, 566 (5.9%) were assessed as having severe disability based on combined evaluation with the two hierarchical models; whereas, of all the long-term caretakers assessed as having moderate disability using the hierarchical model established in the study, 30.1% were assessed as having severe disability according to the evaluation with the National Disability Rating Criteria. ConclusionBased on the analysis using the hierarchical model established in the study, there are some defects in the original hierarchical model adopted by the National Disability Rating Criteria and further researches are needed to address the issue.